2014
DOI: 10.1139/cjfas-2013-0479
|View full text |Cite
|
Sign up to set email alerts
|

Foraging diversity in lactating New Zealand sea lions: insights from qualitative and quantitative fatty acid analysis

Abstract: Lactating New Zealand (NZ) sea lions (Phocarctos hookeri) exhibit different foraging patterns during their foraging trips, with benthic divers spending more energy at sea than mesopelagic conspecifics. We compared blubber fatty acids (FAs) of 14 benthic and 12 mesopelagic females captured at the Auckland Islands, NZ subantarctic, in late January 2000 using an analysis of similarities (ANOSIM). FA profiles between foraging types were significantly different (global R = 0.30, p = 0.001), suggesting a different u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
4
7
0
Order By: Relevance
“…Foraging research has shown this is the case for female NZ sea lions (Chilvers and Wilkinson 2009). The results from this research and Meynier et al (2014), confirms that these foraging ecotypes are also represented by differing stable isotope signatures and therefore likely prey or proportions of prey in diet. Being able to collect and analyse stable isotope composition and therefore identify likely foraging ecotype from blood or a whisker from a female NZ sea lion is a far faster, less invasive and more cost effective option than undertaking foraging studies, meaning the foraging ecotypes of more individuals could be determined.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Foraging research has shown this is the case for female NZ sea lions (Chilvers and Wilkinson 2009). The results from this research and Meynier et al (2014), confirms that these foraging ecotypes are also represented by differing stable isotope signatures and therefore likely prey or proportions of prey in diet. Being able to collect and analyse stable isotope composition and therefore identify likely foraging ecotype from blood or a whisker from a female NZ sea lion is a far faster, less invasive and more cost effective option than undertaking foraging studies, meaning the foraging ecotypes of more individuals could be determined.…”
Section: Discussionsupporting
confidence: 72%
“…fin fish compared with cephalopods). This difference has been suggested from foraging behavioural studies (Chilvers and Wilkinson 2009) and shown in fatty acid analysis (Meynier et al 2014). The mesopelagic foraging females predominantly forage in the waters above the western slopes of the Auckland Island shelf (Chilvers and Wilkinson 2009), which matches the prey distribution of hoki (Macruronus novaezelandiae (Hector, 1871)), and rattails (Coelorinchus spp.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…; Meynier et al . , ; Fowler et al . ), are being used to investigate the diet and foraging ecology of marine predators.…”
mentioning
confidence: 99%